PENDEKATAN BILANGAN BULAT UNTUK PENJADWALAN SEPAK BOLA LIGA ITALIA DENGAN SISTEM ROUND ROBIN TOURNAMENT - , MUHAMMAD FIKRI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Scheduling the Italian major football league or called serie A usually uses round robin tournament. In this Italian football league there are some important constraints must be considered, such as twin-schedules for teams belonging to the same home-town , matches between seeded teams, about TV broadcast and about break. In this final project, we present a mathematics model to derive feasible schedules subject to those constraints. The proposed procedure is divided into three phases